DISTRIBUTION OF BMI-FOR-AGE Z-SCORES BY SEX AND GRADE AMONG STUDENTS AT DAI DONG PRIMARY SCHOOL, NGHE AN PROVINCE IN 2025 - Thi Hong Hanh, Nguyen; My Duyen, Nguyen (HNUE Journal of Science: Journal of Natural Sciences, 2026)
The double burden of malnutrition is an emerging public health challenge in rural Vietnam. The body mass index (BMI)-for-age Z-score (BAZ), based on the WHO 2007 growth reference, provides a continuous metric for nutritional assessment in school-age children. Analyzing BAZ according to school grade is particularly informative because school grade reflects children's cumulative educational and nutritional environments; however, such analyses have remained limited in the Vietnamese literature. This study aimed to describe the distribution characteristics of BAZ and to evaluate differences according to sex and school grade among primary school students at Dai Dong Primary School, Nghe An Province, in 2025. A cross-sectional study was conducted among 887 students (458 boys and 429 girls). BAZ values were calculated using WHO AnthroPlus version 1.0.4. Since BAZ was not normally distributed, non-parametric tests were applied. The results showed that overall median BAZ was −0.356 (interquartile range: −1.109 to 0.643), significantly below the WHO reference median of 0 (p < 0.001). The double burden of malnutrition was evident with 19.2% of students classified as overweight or obese, and 6.5% classified as wasted. Boys had significantly higher BAZ values than girls (−0.223 vs. −0.463; p = 0.020) and a nearly threefold higher prevalence of obesity (10.9% vs. 3.7%; p < 0.001). Significant differences in BAZ were observed across school grades (p = 0.041), with Grade 3 having the highest median BAZ (−0.104), which corresponded to the highest prevalence of overweight/obesity (22.4%). In contrast, the prevalence of wasting increased significantly from Grade 1 (6.3%) to Grade 5 (10.3%) and was highest in Grades 4 and 5 (10.7 and 10.3%, respectively; χ² = 20.33, p < 0.001). A double burden of malnutrition exists in this rural primary school population. Grade 3 exhibited the highest burden of overweight/obesity, while upper grades (4–5) showed a marked increase in wasting, underscoring the need for grade-specific nutritional surveillance and targeted interventions.